The Analysis Study of Prevalence, Risk Factor and Management of Persistent Pain in Intensive Care Survivors: A Comprehensive Systematic Review - Kurniawan, Agung Ganjar; Khairunnisa, Shabrina (International Medical Journal Corp. Ltd, 2024)
Background: Post-intensive care syndrome (PICS), encompass physical, cognitive, and mental health deficits that arise and persist following hospitalization for critical illness. This systematic review aims to evaluate the prevalence, risk factor and management of persistent pain in intensive care survivors by analyzing available studies on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: A large proportion of ICU survivors suffer from physical, mental, and cognitive impairments. Holistic approach to post-ICU care, which includes pain management and psychological support, is essential for improving the overall quality of life of ICU survivors.